Cultural Negotiation in Childcare among Inter-Ethnic Muslim Couples in Magelang Regency - Madyawati, Lilis; Nurjannah, Nurjannah; Hibana, Hibana (Universitas Muhammadiyah Magelang, 2025)
Inter-ethnic marriage influences parenting practices, particularly in multicultural societies like Indonesia. This study analyzes how cultural negotiation shapes parenting among inter-ethnic Muslim couples specifically between Javanese and non-Javanese partners in Borobudur District, Magelang Regency. Using an intrinsic case study approach, data were collected through observation, in-depth interviews, and documentation to explore how these couples develop parenting strategies that integrate local cultural values with Islamic educational principles. Findings reveal that cultural negotiation occurs through two main strategies: compromise and consensus. These processes are shaped by childhood experiences, gender-based power dynamics, and extended family solidarity. The negotiations result in diverse parenting styles, including authoritative, authoritarian, and permissive approaches. This study highlights parenting as a social practice formed through the interplay of cultural dominance and collective solidarity. Theoretically, it contributes to the literature on cross-cultural parenting in Muslim families and offers insights for developing inclusive family education policies in multicultural contexts.